LITERATURE REVIEW OF RESEARCH TRENDS ON AUGMENTED REALITY AS A MEDIA ART THERAPHY FOR PEOPLE WITH DISABILITIES - Noviani, Astri; Nurfarina, Anne (Penerbit Lafadz Jaya, 2023)
Research related to Art Therapy on an international scale increases every year. Several studies identified its development through a bibliometric approach referring to various scientific areas. Research generally describes things that are contextual with visual arts-based scientific products as artistic therapies. On the other hand, this development is supported by technological advances, including Augmented Reality (AR). AR is a technology that allows users to gain additional insight into reality from a situation needed. The correlation between art therapy and AR is a fundamental research platform for research teams in developing learning media for people with disabilities. So that literacy analysis is needed related to the two objects of study. This study will review the literacy characteristics of previous research with the aim of gaining objective insight into AR media for learning for people with disabilities. The method used is a literature study with a Bibliometric Analysis approach adopting the five-stage method from Denyer and Tranfield (2009). Research output in the form of data recommendations and concepts that are of novelty value according to user needs.